Skills for green and just transitions: Reflecting on the role of vocational education and training for sustainable development - Margarita Langthaler; Simon McGrath; Presha Ramsarup (Austrian Foundation for Development Research (ÖFSE), 2021)
The human capability to learn is widely regarded as one of the most important resources for achieving an environmentally and socially sustainable and equitable society. Yet, traditional institutions of learning are lagging behind in transmitting such kind of transformative skills. As for Vocational Education and Training (VET), there is still little debate on what the systemic changes of a transition to a greener economy will mean beyond the provision of specific technical skills. In this Briefing Paper, we aim at providing a critical overview of existing debates on skills for just transitions to a greener economy. In the first section, we will initially discuss the main notions of the green economies and skills discourses. Subsequently, the orthodox approach to VET will be critically analysed and we will outline suggestions for alternative approaches to sustainability and VET. In the second section, we will have a look at the policy level in summarising donor approaches and in giving a brief account of South Africa's experience investigating the responsiveness of the skills system to the green economy. Conclusions will sum up.
Keywords: 330; Green economy; green skills; vocational education and training; just transitions; transformative learning